Pengaruh Pemahaman Bahasa Arab terhadap Penetapan Hukum dalam Fiqh - waluyo, riskywaluyo_jaty (BULETIN ADALAH, 2025)
Abstract: Arabic plays a crucial role in the study of Islamic law because all primary sources the Qur’an, Hadith, ijma’, and qiyas are written in Arabic. Limited understanding of Arabic structures and meanings can lead to misinterpretation of legal texts and incorrect rulings. This study examines how mastery of the Arabic language affects the accuracy of legal reasoning in fiqh. Using a qualitative-descriptive approach, the research shows that skills in syntax (nahwu), morphology (sharaf), rhetoric (balaghah), and style (uslub) greatly influence a jurist’s ability to derive legal rulings. Therefore, Arabic is not just a means of communication but a key tool for fully understanding Islamic law. Keywords: Arabic Language, Fiqh, Legal Derivation, Islamic Law, Ushul Fiqh